THE BENEFITS OF USING DIALOGUE JOURNAL WRITING FOR IMROVING STUDENTSâ WRITING OF PERSONAL LETTER - Aininna, Nur (ELT Forum: Journal of English Language Teaching, 2014)
This study aims at investigating how dialogue journal writing benefits studentsâ writing of personal letter and how significance the resulted improvement is. Personal letter is important for it is used by people in their daily lives in diverse forms. Meanwhile, dialogue journal is chosen as the method for it is powerful to bridge learnersâ needs of supplementary learning times and a private studentâ-teacherâs interaction. The research design of the study is mainly qualitative. However, quantitative analysis is still used to reveal studentsâ overall writing proficiency and the significance of studentsâ improvement. The five writing aspects mentioned by Brown (2004) are used as the basis of both analyses. The qualitative analysis attempts to describe how the students perform the aspects in their writing. Meanwhile, the quantitative analysis tries to assess studentsâ performance of the aspects by giving each aspect a score realization according to the criteria outlined in Brownâs rubric of writing assessment. The results of the analysis show that studentsâ writing improves all the aspects quite well. The biggest improvement lies in the content aspect. Majority of studentsâ earlier writing fails to address the topic of writing. Nonetheless, all of their final writing has already addressed the topic correctly. Meanwhile, the aspect of style and quality of expressions seems to undergo the least improvement. Some vocabularies are still found to be incorrectly used. However, studentsâ later writings exhibit a better sentence variety realized through the use of various cohesive devices. The improvement unfolded in the qualitative analysis is supported by the findings of the quantitative analysis of which all of the twenty students improve their writing scores in the final test. Some scores are even elevated quite significantly. The improvement of the five aspects presented in studentsâ later writing has turned the writing to be more communicative. Therefore, the mastery of the aspects is very beneficial. Since all the five aspects belong to the micro and macro-skills of writing, the teaching of these skills is then imperative to be given.